Pengaruh Inventory Turnover, Sales Growth, dan Liquidity Terhadap Profitabilitas pada PT. Sumber Alfaria Trijaya Tanjung Morawa Periode 2013-2017 - Keumala Hayati; Antonius KAP Simbolon; Renita Ferawati Lumban Gaol; Intan Permata Sari Sianturi; Yosua Michael Sagala (Politeknik Ganesha Medan, 2019)
This research aims to exsplain the effect Inventory Turnover, Sales Growth, and Liquidity on Profitability. This study was conducted at PT. Sumber Alfaria Trijaya Tanjung Morawa in periods of 2013-2017 with a total study population of 60 months. The sampling technique used in this study is sampling jenuh and acquired 60 months samples. The analisys technique used is multiple linear regressions, both t test and F test. The dependent variable is profitability while the independent variable is Inventory Turnover, Sales Growth, and Liquidity